The Dilemma of AI Surveillance In the Rule of Law: Challenges to Privacy Rights and Civil Liberties from the Perspectives of International and Asean Law - Samuel Febriyanto (Pengurus Pusat Perkumpulan Ilmuwan Administrasi Negara Indonesia (PIANI), 2026)
The implementation of Artificial Intelligence–based surveillance technologies (AI Surveillance), such as facial recognition and predictive behavioral analysis, has become a primary instrument in maintaining national security. However, the use of these technologies frequently comes into conflict with the protection of human rights. This study is motivated by the growing risk of state transformation into a surveillance state capable of conducting mass and automated monitoring of citizens, which may undermine the right to privacy and restrict anonymous freedom of expression in public spaces. The research addresses two main questions: (1) What international standards govern the limitation of AI Surveillance to prevent violations of the right to privacy? and (2) How do ASEAN countries comparatively regulate the accountability of governmental use of surveillance technologies? This research employs a normative juridical method, utilizing a conceptual approach to examine theories of privacy in the digital era, a statutory approach through the analysis of international legal instruments such as the International Covenant on Civil and Political Rights (ICCPR), and a comparative approach focusing on ASEAN countries, particularly Indonesia, Singapore, and the Philippines. The findings indicate that most regulatory frameworks in the ASEAN region continue to grant excessively broad discretion to states to conduct surveillance under the justification of national security, often without independent judicial oversight mechanisms. The study concludes that a significant legal gap exists in mitigating discriminatory abuses of AI Surveillance. Accordingly, this research recommends the establishment of a strict “necessity and proportionality test” for all uses of AI in public surveillance, as well as the strengthening of the independence of data protection supervisory authorities at the regional ASEAN level.